Pyoderma gangrenosum, diagnostic and therapeutic difficulties – two cases imitating breast cancer - Tupikowska, Małgorzata; Kaniowski, Michał; Gruber, Joanna; Musioł, Michał; Maj, Joanna (Dermatology Review/Przegląd Dermatologiczny, 2016)
Introduction . Pyoderma gangrenosum is a rare dermatosis with unknown etiology. Painful and quickly spreading ulcerations with necrotic bottom and heaped wound edges are typical. Objective . The aim of this study is to present patients with pyoderma gangrenosum which imitated breast cancer and their treatment. Case report . Two women suspected of having breast cancer developed painful and non-healing ulceration after surgical excision of nodules. Although in histopathology mastopathic changes were described, the diagnosis was verified and subsequent biopsies showed no cancerous changes. Ulcerations were treated as an infectious surgery complication. The diagnosis of pyoderma gangrenosum was made on the basis of characteristic anamnesis, clinical features and histopathological examination. In the treatment cyclosporine with dapsone and cyclosporine with glucocorticosteroids were used and a very quick local response and pain relief were obtained. Conclusions . The presented cases illustrate diagnostic difficulties and the role of the pathergy phenomenon in the development of pyoderma gangrenosum lesions. The course and treatment of the disease in both cases also reveal the ineffectiveness of monotherapy with glucocorticosteroids.